Pelatihan Database bagi Siswa SMA Harapan Kasih Bandung - Wong, Hendry; Wijaya, Marvin Chandra; Loekito, Jimmy Agustian; Pelupessy, Donny Stefanus; Davidy, Adriel Elmer; Bunardy, Yohanes Noel; Hendrajaya, Calvin; Cheol, Shin Min; Ryadi, Fyane Angelica; Wong, Karenina (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Currently, computer literacy is very necessary to be studied by various parties, including high school students. Information and Communication Technology (ICT) subject matter at high school level has been studied, but usually only basic programming. Currently, lessons about databases using SQL are also required to be studied at the high school level, but due to limited curriculum, resources and time, this material is usually not studied. Therefore, the solution is to provide training outside of school hours. SMA Harapan Kasih Bandung, collaborates with Maranatha Christian University to provide computer training with material about databases. The training method used is face-to-face in a computer laboratory. The face-to-face procedure is by giving an initial test, theoretical explanation, practical explanation, student practice and final test. Face to face is given for two hours for each class. Training results are evaluated in terms of knowledge and skills. The evaluation results of this database training have been satisfactory with an absorption rate of more than 80%.